SMARTTRAN SOFTWARE FOR TRANSPORTATION OF OIL JSC KAZTRANSOIL - Minglibayev Mukhtar Zhumabekovich; Omarov Chingis Tukenovich; Ibraimova Aigerim (Academic Journal of Physical and Chemical Sciences, 2020)
Digital technology for monitoring, controlling and optimizing technological practices of oil and oil mixtures pumping through the sections of main pipelines, operating pumping units, preheaters, ground temperature, oil rheological properties and etc. has been created in a result of integration of a SmartTran software with of the Supervisory Control and Data Acquisition (SCADA) and the Automated Metering System (AMS) systems of the JSC “KazTransOil”. The paper describes the main functionalities of the SmartTran software which was developed by the authors. Thermohydraulic calculations of the sections of the main oil pipelines of JSC “KazTransOil” were carried out and compared with the actual data on the distribution of oil pressure, oil and ground temperature, power consumption of pumping equipment taken from SCADA and AMS. The accordance of the calculated and actual data shows the applicability of the SmartTran software for the automation of calculations, planning and optimization of the technological modes of oil transportation through the main oil pipelines of JSC “KazTransOil”.